Bulletproof ceramic material with wave permeability and preparation method thereof

By introducing high-purity silicon nitride powder and other auxiliary materials into the elastic-resistant ceramic materials and adjusting the sintering process, the problem of poor wave transmissibility of existing elastic-resistant ceramic materials is solved, and the high wave transmissibility and elastic-resistant performance are achieved. Suitable for protection of military communication equipment.

CN119430885APending Publication Date: 2025-02-14扬州北方三山工业陶瓷有限公司

Patent Information

Application Number
CN202411679333.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

During the sintering process, existing elastic-resistant ceramic materials need to be added with sintering additives such as carbon black, which makes it difficult to meet the needs of wave transmissibility, which will produce extremely strong signal shielding and affect military communications.

Method used

By introducing high-purity silicon nitride powder on the basis of alumina micropowder, and combining magnesium carbonate powder and lanthanum oxide powder, the material composition and sintering process are adjusted to reduce the dielectric constant of the material and improve the wave transmittance performance.

Benefits of technology

It realizes high wave transmissibility and excellent elastic resistance of ceramic materials, avoids signal shielding, and is suitable for protection of military communication equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430885A_ABST
    Figure CN119430885A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of ceramic materials, and discloses a wave-transparent bulletproof ceramic material and a preparation method thereof. The ceramic material comprises the following components in parts by weight: 60-80 parts of alumina micro powder, 20-40 parts of silicon nitride powder, magnesium carbonate powder, lanthanum oxide powder, a polyethylene glycol dispersant, a temporary binder emulsified paraffin and glycerol. The preparation method comprises the following steps: mixing and stirring the raw materials, and fully pulping; grinding and dispersing the slurry through a high-speed grinder; carrying out spray granulation on the slurry by adopting a centrifugal spray granulation tower, and preparing the slurry into composite granulation powder; pressing the granulation powder into a required shape to obtain a green body; and a high-temperature nitrogen gas pressure sintering furnace is adopted for product sintering. The bulletproof ceramic disclosed by the invention has the advantages of low dielectric constant, high toughness and high hardness, and normal communication signal transmission is not influenced while the bulletproof ceramic has excellent protection performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of ceramic materials, and in particular to a wave-transmissive bulletproof ceramic material and a preparation method thereof. Background Art

[0002] With the development of military information technology, the need for protection of military communication radars, especially electronic devices exposed on the surface of equipment, is becoming more and more urgent. In order to improve the anti-strike capability of military communication equipment, it is crucial to add anti-ballistic protection without signal shielding.

[0003] The commonly used anti-ballistic ceramics are mainly high-purity alumina ceramics, silicon carbide-based ceramics and boron carbide-based ceramics. Since silicon carbide and boron carbide materials have high dielectric constants, sintering aids such as carbon black need to be added during the ceramic sintering process, which makes it difficult for these two anti-ballistic ceramics to meet the demand for wave transmission, resulting in extremely strong signal shielding and communication barriers.

[0004] At present, the commonly used wave-transmitting radome materials are mostly inorganic fiber composite materials, such as quartz glass fiber composite materials, aramid fiber composite materials, etc. Some special radome materials are mainly porous silicon nitride-based composite materials. However, wave-transmitting and bullet-resistant ceramic materials have not yet appeared. Therefore, the development of a bullet-resistant ceramic with high hardness, high toughness and high wave transmission is of great significance to military communication protection. Summary of the invention

[0005] Purpose of the invention: In view of the deficiencies in the prior art, the present application provides an anti-ballistic ceramic with high wave transmittance and excellent mechanical properties.

[0006] Technical solution: The present application provides a wave-transmitting bulletproof ceramic material, which is composed of 60-80 parts of alumina powder, 20-40 parts of silicon nitride powder, and additional magnesium carbonate powder, lanthanum oxide powder, polyethylene glycol dispersant, temporary binder emulsified paraffin, and glycerol; the alumina powder: alumina purity> 99.8%, α-phase content higher than 96%, original crystal size< 0.6μm, Na2O content< 0.03%; the silicon nitride powder: purity> 98%, micropowder particle size D50=1.5μm, oxygen content< 0.5%.

[0007] As a basic material, high-purity (>99.8%) alumina powder has excellent mechanical strength, hardness and corrosion resistance, and is an important component of anti-ballistic materials. A high α-phase content (>96%) means that the material is more stable and less prone to phase change, thereby maintaining good physical properties. A small original crystal size (<0.6μm) helps to improve the density and strength of the material. Therefore, the high-purity ultrafine alumina powder is preferably: alumina purity>99.8%, α-phase content higher than 96%, original crystal size<0.6μm, and Na2O content<0.03%.

[0008] Silicon nitride is a very hard and high temperature resistant material. The present invention, by adding silicon nitride, grows inside the ceramic to form a columnar structure, thereby improving the fracture toughness of the ceramic. In addition, the hardness of silicon nitride itself is also relatively high, which will not seriously reduce the hardness of the ceramic and maintain the anti-ballistic performance of the ceramic. In the present invention, silicon nitride powder is added to alumina bulletproof ceramics, and the dielectric constant of the entire ceramic is reduced by the low dielectric constant characteristics of silicon nitride, thereby improving the electromagnetic wave permeability. In addition, silicon nitride has a lower density, which helps to reduce the weight of the overall material, and its good thermal stability also enables the material to maintain good performance at high temperatures. The micro-powder size (D50 = 1.5 μm) and low oxygen content (<0.5%) of silicon nitride ensure the purity and uniformity of the material. Therefore, the silicon nitride powder is preferably: purity> 98%, micro-powder size D50 = 1.5 μm, oxygen content < 0.5%.

[0009] As a sintering aid, magnesium carbonate powder can reduce the sintering temperature, promote the bonding between particles, and improve the density of the material. Lanthanum oxide powder not only improves the density, but also improves the microstructure and enhances the mechanical properties of the material. Lanthanum oxide powder can improve the wave transmission of the material and reduce the signal shielding effect, which is especially important for anti-ballistic materials that require wave transmission. The synergistic effect of magnesium carbonate powder and lanthanum oxide powder enables the material to have good wave transmission performance while maintaining high strength.

[0010] Through these synergistic effects, the final composite ceramic material not only has excellent anti-ballistic performance, but also has good wave transmittance and lightweight characteristics, and is suitable for a variety of high-performance application fields.

[0011] Specifically, 0.1-0.3 parts of magnesium carbonate powder, 0.2-0.4 parts of lanthanum oxide powder, 1.4-1.6 parts of polyethylene glycol dispersant, 9-11 parts of temporary binder emulsified paraffin, and 0.5-1.5 parts of glycerol are added. Preferably, 0.2 parts of magnesium carbonate powder, 0.3 parts of lanthanum oxide powder, 1.5 parts of polyethylene glycol dispersant, 10 parts of temporary binder emulsified paraffin, and 1 part of glycerol are added.

[0012] The present invention also provides a method for preparing the above-mentioned bulletproof ceramic material with wave-transmitting properties, comprising the following steps:

[0013] Step 1: Pulping: Add deionized water to the mixing barrel, start the mixing barrel, and then accurately weigh the raw materials according to the ratio, and then add the weighed raw materials into the mixing barrel in turn, stirring for 1-2 hours to fully slurry them;

[0014] Step 2: Fine grinding: Grind and disperse the slurry through a high-speed grinder;

[0015] Step 3: spray granulation: spray granulate the slurry using a centrifugal spray granulation tower to prepare the slurry into composite granulation powder;

[0016] Step 4: Dry pressing: Press the granulated powder into the desired shape to obtain a green embryo;

[0017] Step 5: High temperature sintering: Use a high temperature nitrogen pressure sintering furnace to sinter the product.

[0018] Specifically, in step 1, the raw material ratio is: 60-80 parts of alumina powder, 20-40 parts of silicon nitride powder, 0.2 parts of magnesium carbonate powder, 0.3 parts of lanthanum oxide powder, 1.5 parts of polyethylene glycol dispersant, 10 parts of temporary binder emulsified paraffin, 1 part of glycerol, and 100 parts of deionized water.

[0019] Specifically, in step 2, the spindle speed is controlled at 1200-1400r / min, and the grinding medium is alumina balls. When the coarse end particle size of the slurry D97 <1.8μm, stop grinding and discharge the slurry. Grind and disperse through a high-speed grinder, and strictly control the coarse end particle size of the micropowder. Make the coarse end particle size lower than 1.8μm and significantly reduce the sintering temperature. The sintering temperature of ordinary alumina is 1650℃, and the sintering temperature is reduced by more than 150℃. On the one hand, it refines the ceramic grains, avoids abnormal grain growth, and maintains the high performance of the material; on the other hand, it can inhibit the high-temperature decomposition of silicon nitride, and play the role of silicon nitride in reducing the dielectric constant of the material and improving the toughness of the material.

[0020] Specifically, in step 3, the main parameters of spray granulation are: air inlet temperature 190±5℃, air outlet temperature 90±3℃, centrifugal disc speed 1800r / min. The main indicators of granulation: bulk density 0.98g / cm 3 , fluidity 32s / 30g, moisture 0.5%.

[0021] High temperature sintering is a process in which particles in the green body undergo solid phase diffusion and recrystallization by high temperature heating in a high temperature nitrogen pressure sintering furnace. The gaps between particles gradually decrease, and a dense ceramic material is eventually formed. Nitrogen pressure sintering can prevent the material from oxidizing at high temperatures, while providing a certain amount of pressure, which helps to increase density.

[0022] Specifically, in step 4, a four-column hydraulic press is used for compression molding.

[0023] As a further improvement, in step 4, the green embryo after dry pressing is not directly subjected to high-temperature sintering, but is subjected to impregnation and pre-cracking treatments before being subjected to high-temperature sintering.

[0024] Specifically, the green body after dry pressing is immersed in liquid polysilazane (PSZ) under vacuum conditions for 20 to 24 hours. After the impregnation is completed, the excess polymer is dried to remove it, and it is cured at 120°C. After curing, it is pre-cracked in a nitrogen atmosphere at a pre-cracked temperature of 600°C for 2 hours to remove some volatile substances and reduce thermal stress and crack formation during subsequent high-temperature sintering. The ceramic material treated by this improved method can more finely control the microstructure and composition of the material, thereby further optimizing its wave transmission performance. In addition, according to the density and performance requirements of the required material, the impregnation and cracking process can be repeated many times to gradually fill the pores in the green body and improve the density and uniformity of the material.

[0025] In the present invention, the fifth step of high temperature sintering is a key step, which can significantly improve the density, strength and toughness of the material. Nitrogen pressure sintering can also improve the wave transmission of the material and reduce the signal shielding effect. The specific control process is as follows:

[0026] Starting from room temperature, heat up to 800°C at a rate of 3°C / min, keep at 800°C for 30 min, and the vacuum degree is <50Pa; then heat up to 1300°C at a rate of 2°C / min, keep at 1300°C for 60 min, and the vacuum degree is <50Pa; then, heat up to 1480°C at a rate of 1.5°C / min, and keep at 1480±20°C for 300 min.

[0027] Furthermore, in the process of 1300-1480℃, the specific operation is as follows: after the temperature rises to 1300℃, start to charge nitrogen, and the charging rate is maintained at 0.01MPa / min. When the temperature rises to 1480±20℃, the nitrogen pressure in the furnace is maintained at 1.2±0.2MPa. After keeping at 1480℃ for 60min, charge nitrogen again at a charging rate of 0.1MPa / min. After keeping at 1480℃ for 120min, the nitrogen pressure in the furnace is maintained at 7.2±0.2MPa. Then stop charging nitrogen, and the pressure in the furnace is maintained at 7±0.3MPa until the end of the insulation.

[0028] During the process at room temperature -800℃, vacuum heating is adopted to fully decompose the organic matter (emulsified wax, dispersant, propylene glycol, etc.) inside the ceramic body to avoid carbonization residues that would reduce the performance of the ceramic.

[0029] During the process of 800-1300℃, pre-sintering is carried out. At this time, the ceramic material has not yet sintered and shrunk, and has a loose porous structure. At this time, vacuum is maintained to further remove organic matter in the green body.

[0030] During the process of 1300-1480℃, the ceramics begin to sinter and shrink after 1300℃, and silicon nitride may begin to decompose. In order to avoid the decomposition of silicon nitride, nitrogen is filled into the furnace to inhibit the decomposition of silicon nitride by increasing the nitrogen pressure. After 60 minutes of heat preservation at 1480℃, the ceramics are sintered more densely, changing from a loose porous structure to a closed pore structure inside. At this time, increasing the nitrogen pressure, by forming a high pressure around the ceramic, on the one hand, inhibits the decomposition of silicon nitride, and on the other hand, relies on the pressure to help remove the closed pores, thereby improving the sintering density of the ceramic.

[0031] Beneficial effects: The present invention adjusts the material composition ratio, uses aluminum oxide as the base material and introduces silicon nitride powder with a low dielectric constant, which can significantly reduce the overall dielectric constant of the material, reduce the dielectric loss when electromagnetic waves pass through, and thus improve the material's wave transmission performance. This ensures that even if an anti-bullet layer is added to the surface of the equipment, it will not affect the normal communication signal transmission.

[0032] The present invention not only takes into account the material's anti-elasticity and wave-transmitting properties, but also takes into account the material's processing properties. For example, using auxiliary materials such as dispersants and binders in a specific proportion helps improve the material's fluidity and molding properties, making the entire preparation process smoother and the quality of the final product more stable and reliable.

[0033] The present invention uses a special sintering process, including negative pressure degreasing, pre-sintering and high-temperature sintering steps, to ensure that the changes in the physical and chemical properties of the material at different stages meet the expected goals, so that the final product can adapt to the use requirements in various harsh environments, including extreme conditions such as high temperature and high pressure.

[0034] The bulletproof ceramic material of the present invention is particularly important for military communication equipment and can protect internal electronic equipment from damage in extreme environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a sample photo of the ceramic material obtained in Example 1.

[0036] Figure 2 This is a fracture morphology photograph of the ceramic material obtained in Example 1.

[0037] Figure 3 This is a fracture morphology photograph of the ceramic material obtained in Example 3. DETAILED DESCRIPTION

[0038] The technical solution of the present application is described in detail below through embodiments, but the protection scope of the present application is not limited to the embodiments.

[0039] Embodiment 1:

[0040] 60 parts of alumina powder, 40 parts of silicon nitride powder, 0.2 parts of magnesium carbonate powder, 0.3 parts of lanthanum oxide powder, 1.5 parts of polyethylene glycol dispersant, 10 parts of temporary binder emulsified paraffin, 1 part of glycerol, and 100 parts of deionized water.

[0041] Step 1: Add 100 parts of deionized water into the mixing barrel, then add the weighed raw materials into the mixing barrel in turn, and stir thoroughly for 1.5 hours to make each material into a uniform slurry;

[0042] Step 2: Grind and disperse the slurry using a high-speed grinder with a spindle speed of 1300r / min. The particle size of the slurry after grinding is D50=0.54μm, D97=1.78μm;

[0043] Step 3: Spray granulation, main parameters: air inlet temperature 190±5℃, air outlet temperature 90±3℃, centrifugal disc speed 1800r / min. Main indicators of spray granulation powder: bulk density 0.98g / cm 3 , fluidity 32s / 30g, moisture 0.5%;

[0044] Step 4: Pressing and molding, green density 2.1g / cm 3 ;

[0045] Step 5: High temperature sintering. The sintering system is as follows:

[0046] Negative pressure degreasing: heating rate 3℃ / min, room temperature -800℃, 800℃ insulation for 30min, vacuum degree <50Pa;

[0047] Pre-sintering: heating rate 2℃ / min, 800-1300℃, 1300℃ insulation for 60min, vacuum degree <50Pa;

[0048] Sintering: Heating rate 1.5℃ / min, 1300-1500℃, 1500℃ insulation for 300min. After the temperature rises to 1300℃, start to charge nitrogen, and the charging rate is maintained at 0.01MPa / min. When the temperature rises to 1500℃, the nitrogen pressure in the furnace is maintained at 1.2±0.2MPa. After 60min of insulation at 1500℃, charge nitrogen again, and the charging rate is 0.1MPa / min. After 120min of insulation, the nitrogen pressure in the furnace is maintained at 7.2±0.2MPa. Then stop charging nitrogen, and the pressure in the furnace is maintained at 7±0.3MPa until the insulation ends.

[0049] The sample photos of the obtained ceramic material are as follows Figure 1 shown.

[0050] Performance testing:

[0051] Ceramic density: 3.5-3.6g / cm 3; Ceramic flexural strength: 550-680MPa; Ceramic fracture toughness: 5.5-6.5MPa·m1 / 2; Rockwell hardness: 88-89, wave transmittance 98.5%.

[0052] The fracture morphology of the obtained ceramic material (2.5 μm) is shown in Figure 2 As shown,

[0053] Embodiment 2:

[0054] 80 parts of alumina powder, 20 parts of silicon nitride powder, 0.2 parts of magnesium carbonate powder, 0.3 parts of lanthanum oxide powder, 1.5 parts of polyethylene glycol dispersant, 10 parts of temporary binder emulsified paraffin, 1 part of glycerol, and 100 parts of deionized water.

[0055] Step 1: Add 100 parts of deionized water into the mixing barrel, then add the weighed raw materials into the mixing barrel in turn, and stir thoroughly for 1.5 hours to make each material into a uniform slurry;

[0056] Step 2: Grind and disperse the slurry using a high-speed grinder with a spindle speed of 1300r / min. The particle size of the slurry after grinding is D50=0.48μm, D97=1.66μm;

[0057] Step 3: Spray granulation, main parameters: air inlet temperature 190±5℃, air outlet temperature 90±3℃, centrifugal disc speed 1800r / min. Main indicators of spray granulation powder: bulk density 1.02g / cm 3 , fluidity 28s / 30g, moisture 0.6%;

[0058] Step 4: Pressing and molding, green density 2.2g / cm 3 ;

[0059] Step 5: High temperature sintering. The sintering system is as follows:

[0060] Negative pressure degreasing: heating rate 3℃ / min, room temperature -800℃, 800℃ insulation for 30min, vacuum degree <50Pa;

[0061] Pre-sintering: heating rate 2℃ / min, 800-1300℃, 1300℃ insulation for 60min, vacuum degree <50Pa;

[0062] Sintering: Heating rate 1.5℃ / min, 1300-1480℃, 1480℃ insulation for 300min. After the heating starts at 1300℃, start filling with nitrogen, and the pressure rate is maintained at 0.01MPa / min. When the temperature rises to 1500℃, the nitrogen pressure in the furnace is maintained at 1.2±0.2MPa. After 60min of insulation at 1480℃, fill with nitrogen again, and the pressure rate is 0.1MPa / min. After 120min of insulation, the nitrogen pressure in the furnace is maintained at 7.2±0.2MPa. Then stop filling with nitrogen, and the pressure in the furnace is maintained at 7±0.3MPa until the insulation ends.

[0063] Performance testing:

[0064] Ceramic density: 3.65-3.75g / cm 3 ; Ceramic flexural strength: 430-520MPa; Ceramic fracture toughness: 4.5-5.5MPa·m1 / 2; Rockwell hardness: 88-89; Dielectric constant 2-4; Wave transmittance 97.5%.

[0065] Example 3

[0066] The basic steps of Example 3 are substantially the same as those of Example 1, except that the fourth step is: the green body after dry pressing is immersed in liquid polysilazane (PSZ) under vacuum conditions for 24 hours, cured at 120°C for 2 hours, and then pre-cracked in a nitrogen atmosphere at a pre-cracked temperature of 600°C for 2 hours.

[0067] Performance testing:

[0068] Ceramic density: 3.6-3.8g / cm 3 ; Ceramic flexural strength: 550-680MPa; Ceramic fracture toughness: 5.5-6.5MPa·m1 / 2; Rockwell hardness: 88-89, wave transmittance 99.1%.

[0069] The fracture morphology of the obtained ceramic material (2.5 μm) is shown in Figure 3 As shown,

[0070] Example 4

[0071] The basic steps of Example 4 are substantially the same as those of Example 1, except that the fourth step is: the green body after dry pressing is immersed in liquid polysilazane (PSZ) under vacuum conditions, immersed for 24 hours, cured at 120°C for 2 hours, and then pre-cracked in a nitrogen atmosphere at a pre-cracked temperature of 600°C for 2 hours. It is immersed in liquid polysilazane (PSZ) again under vacuum conditions, immersed for 24 hours, cured at 120°C for 2 hours, and then pre-cracked in a nitrogen atmosphere at a pre-cracked temperature of 600°C for 2 hours.

[0072] Performance testing:

[0073] Ceramic density: 3.7-3.8g / cm 3 ; Ceramic flexural strength: 550-680MPa; Ceramic fracture toughness: 5.5-6.5MPa·m1 / 2; Rockwell hardness: 88-89, wave transmittance 98.9%.

[0074] The above description is only a preferred embodiment of the present application and is not intended to limit the present application.

Claims

1. A wave-transmitting bulletproof ceramic material, characterized in that: The composition is as follows by mass fraction: 60-80 parts of aluminum oxide powder, 20-40 parts of silicon nitride powder, magnesium carbonate powder, lanthanum oxide powder, polyethylene glycol dispersant, temporary binder emulsified paraffin, glycerol; The alumina powder has: alumina purity>99.8%, α-phase content higher than 96%, original crystal size<0.6μm, Na2O content<0.03%; the silicon nitride powder has: purity>98%, powder particle size D50=1.5μm, oxygen content<0.5%.

2. The wave-transmitting bulletproof ceramic material according to claim 1, characterized in that: Add 0.1-0.3 parts of magnesium carbonate powder, 0.2-0.4 parts of lanthanum oxide powder, 1.4-1.6 parts of polyethylene glycol dispersant, 9-11 parts of temporary adhesive emulsified paraffin, and 0.5-1.5 parts of glycerol.

3. The method for preparing the wave-transmitting bulletproof ceramic material according to claim 1, characterized in that: The following steps are involved: Step 1: Pulping: Add deionized water to the mixing barrel, start the mixing barrel, and then accurately weigh the raw materials according to the ratio, and then add the weighed raw materials into the mixing barrel in turn, stirring for 1-2 hours to fully slurry them; Step 2: Fine grinding: Grind and disperse the slurry through a high-speed grinder; Step 3: spray granulation: spray granulate the slurry using a centrifugal spray granulation tower to prepare the slurry into composite granulation powder; Step 4: Dry pressing: Press the granulated powder into the desired shape to obtain a green embryo; Step 5: High temperature sintering: Use a high temperature nitrogen pressure sintering furnace to sinter the product.

4. The preparation method according to claim 3, characterized in that: In step 1, the raw material ratio is: 60-80 parts of alumina powder, 20-40 parts of silicon nitride powder, 0.2 parts of magnesium carbonate powder, 0.3 parts of lanthanum oxide powder, 1.5 parts of polyethylene glycol dispersant, 10 parts of temporary binder emulsified paraffin, 1 part of glycerol, and 100 parts of deionized water.

5. The preparation method according to claim 3, characterized in that: In the second step, the spindle speed is controlled at 1200-1400r / min, the grinding medium is alumina balls, and when the coarse end particle size of the slurry D97 <1.8μm, the grinding is stopped and the slurry is discharged.

6. The preparation method according to claim 3, characterized in that: In step 3, the main parameters of spray granulation are: air inlet temperature 190±5℃, air outlet temperature 90±3℃, centrifugal disc speed 1800r / min.

7. The preparation method according to claim 3, characterized in that: In step 3, the main indicators of granulation are: bulk density 0.98g / cm 3 , fluidity 32s / 30g, moisture 0.5%.

8. The preparation method according to claim 3, characterized in that: In the fourth step, a four-column hydraulic press is used to press the granulated powder into a desired shape, and the formed green body is immersed in liquid polysilazane under vacuum conditions for 20 to 24 hours. After the impregnation is completed, the excess polymer is removed by drying, and the mixture is cured at 120±5°C. After curing, the mixture is pre-cracked in a nitrogen atmosphere at a temperature of 600±5°C for 2 to 3 hours.

9. The preparation method according to claim 3, characterized in that: In step 5, the sintering control process is as follows: starting from room temperature, heating to 800°C at a rate of 3°C / min, keeping at 800°C for 30 minutes, and the vacuum degree is <50Pa; then heating to 1300°C at a rate of 2°C / min, keeping at 1300°C for 60 minutes, and the vacuum degree is <50Pa; then heating to 1480°C at a rate of 1.5°C / min, and keeping at 1480±20°C for 300 minutes.

10. The preparation method according to claim 8, characterized in that: During the process of 1300-1480℃, the specific operation is as follows: after the temperature rises to 1300℃, start to charge nitrogen, and the charging rate is maintained at 0.01MPa / min. When the temperature rises to 1480±20℃, the nitrogen pressure in the furnace is maintained at 1.2±0.2MPa. After keeping at 1480℃ for 60min, charge nitrogen again at a charging rate of 0.1MPa / min. After keeping at 1480℃ for 120min, the nitrogen pressure in the furnace is maintained at 7.2±0.2MPa. Then stop charging nitrogen, and the pressure in the furnace is maintained at 7±0.3MPa until the end of the insulation.

Citation Information

Patent Citations

  • High-strength special ceramic and preparation method thereof

    CN106673624A

  • Method for preparing low-cost high-strength aluminum oxide ceramic substrate for electronic packaging

    CN106810214A

  • AlO-SiCN complex phase ballistic ceramic and preparation method thereof

    CN108863321A

  • Alumina bulletproof ceramic and preparation method thereof

    CN115073145A

  • Preparation method of silicon nitride closed-pore heat-insulating ceramic

    CN117024156A

Cited By

  • Method for preparing high-toughness wave-absorbing integrated SiC / Si3N4 composite ceramic in short period

    CN120647394A

  • Preparation method of large-size alumina-based anti-bullet ceramic

    CN121202543A